The Impact of Phonics on Reading Ability - A Social Justice Perspective: Implementation of a Phonics Approach to Teaching Reading in a Remote District of Nepal. - Ransom, Joy (Journal of NELTA, 2025)
Literacy is key to enabling everyone to participate in, and contribute to, society. Education is considered a human right and reading ability an issue of social justice, linked negatively with lifelong disadvantage. Recognizing the  scarcity of research into the practice of teaching reading in schools in Nepal, this study aims to provide evidence to show that learning to read in English is facilitated by knowledge of phonic sounds, blending and decoding. Through a participatory action research design, the impact of phonics instruction on the reading ability of students in rural schools in Lamjung district of Nepal is tracked. Comparisons between progress of students taught by different teaching methods suggest support for the premise that phonics instruction is an effective method of raising reading attainment, enabling all students to read. Factors affecting reading progress are considered through analysis of the data. Perceived barriers to reading proficiency such as negative home situation, low socioeconomic status and gender are shown to be mitigated by effective phonics instruction. Teacher motivation and expertise alongside student attendance are found to be the main determinants of success.